Application of Character Education in the Modern Islamic Boarding School Curriculum - Suhara, Djenal; Nurjanah, Nurjanah; Rusnaya, Manggun; Tarsa, Harsa; Bella, Citra; Hartini, Yeyen (PT. BATARI EDU CALYA, 2024)
Character education is an important aspect in students' personal development, especially in a modern pesantren environment that integrates religious and general education. This study aims to explore the application of character education in the modern pesantren curriculum and its impact on student development. The method used is a case study on several modern Islamic boarding schools in Indonesia, focusing on the strategy, implementation, and evaluation of character education programs. The results of the study show that modern Islamic boarding schools apply various approaches in educating students' character, including the integration of religious values, experiential learning, and extracurricular activities that support character development. The implementation has a positive impact on student attitudes and behaviors, such as increased discipline, responsibility, and empathy. This study concludes that the curriculum of modern Islamic boarding schools that integrate character education can make a significant contribution to the formation of students' character, and recommends a more structured and sustainable approach to improve the effectiveness of character education in Islamic boarding schools.